Notes on the subjective camera and the theory of enunciation - Eugeni, Ruggero; Guerra, Michele (E|C, 2020)
In this paper we intend to formulate some hypotheses about the contributions that a theoretical reflection on the audiovisual can provide to a semiotics of textual enunciation. In order to do this, we will focus our attention on the cinematographic and audiovisual subjective.